Long-term safety and efficacy of intralesional injection of triamcinolone acetonide for sternal keloid pain and pruritis: A double-blind comparison of two concentrations - Babita Ghai; Dipika Bansal; Shyam KS Thingnam (Indian Journal of Pain, 2013)
Background: Intralesional injection of triamcinolone acetonide (TAC) is the most frequently used treatment modality for keloids or hypertrophic scars. However, 20 mg/mL, triamcinolone is reported to have 50% incidence of adverse sequelae. We compared the long-term safety and efficacy of 10 mg/mL with 20 mg/mL intralesional injection of TAC on sternal keloid pain. Methods: Thirty adult patients presenting with pain and/or pruritis at sternal keloid site were randomized into one of the two groups. In group T20 patient received 1 mL of 20 mg/mL TAC, whereas in group T10 patients received 1 mL of 10 mg/mL of TAC intralesional every 2 weeks for a total of 3-4 treatments. Visual analog scale (VAS) scores for pain and pruritis, keloid/scar height, and any adverse sequelae were recorded at 2 weeks interval till 2 months and then at 6, 12, and 15 months. Primary outcome of the study was the percentage of patient developing side effects. Secondary outcome measures were VAS score for pain and itching, keloid height, and recurrence rate of pain or itching. Results: There was a significant decrease in VAS score for pain, pruritis, and keloid height after drug administration in both groups. Side effects was observed in 6 (40%) patients in group T20 and 1 (6.7%) patients in group T10 (P = 0.04). Two patients (13.3%) in group T20 and one in group T10 (6.7%) did not have any improvement in their pain/pruritis scores. Recurrence rate was 13.3% (2 patients) in T20 group compared with 20% (3 patients) in group T10 at 15 months after initial response. Conclusion: Intralesional injection of TAC in concentration of 10 mg/mL is as efficacious as 20 mg/mL for sternal keloid pain but is associated with significantly less side effects.